Flt3- and Tie2-Cre tracing identifies regeneration in sepsis from multipotent progenitors but not hematopoietic stem cells - Fanti, Ann-Kathrin; Busch, Katrin; Greco, Alessandro; Wang, Xi; Ćirović, Branko; Shang, Fuwei; Nizharadze, Tamar; Frank, Larissa; Barile, Melania; Feyerabend, Thorsten B.; Höfer, Thomas; Rodewald, Hans-Reimer (Cell stem cell, 2023)
In response to infections and stress, hematopoiesis rapidly enhances blood and immune cell production. The stage within the hematopoietic hierarchy that accounts for this regeneration is unclear under natural conditions in vivo. We analyzed by differentiation tracing, using inducible Tie2- or Flt3-driven Cre recombinase, the roles of mouse hematopoietic stem cells (HSCs) and multipotent progenitors (MPPs). During polymicrobial sepsis, HSCs responded transcriptionally and increased their proliferation and cell death, yet HSC differentiation rates remained at steady-state levels. HSC differentiation was also independent from the ablation of various cellular compartments-bleeding, the antibody-mediated ablation of granulocytes or B lymphocytes, and genetic lymphocyte deficiency. By marked contrast, the fate mapping of MPPs in polymicrobial sepsis identified these cells as a major source for accelerated myeloid cell production. The regulation of blood and immune cell homeostasis by progenitors rather than stem cells may ensure a rapid response while preserving the integrity of the HSC population.